Pendampingan Pelatihan Keberlanjutan Inovasi Produk Bagi UMKM - Safitri, Anni; Aji, Kresna Rahma; Sholikah, Mar’atus; Sudarmin, Sudarmin (Jaanur ElBarik Indonesia, 2025)
This community service activity aims to help small and medium enterprises (MSMEs) meet customer needs and adapt to rapidly changing market trends. The method of this mentoring activity is through training and mentoring. The results of the mentoring activity indicate that the training is very beneficial for participants. Participants' enthusiasm for the training is demonstrated by the high level of participation and attention; this improves participants' understanding and skills. Furthermore, reports of increased revenue reported by participants and new employee applications indicate that the training also helps companies grow. This demonstrates the importance of product innovation training in driving sustainable MSME growth. Researchers found that small and medium enterprises (MSMEs) in Tunggul Village will be better able to meet customer needs if product innovation training is continuously provided.